MEDIA BERINDIKATOR WARNA SEBAGAI PENDETEKSI Salmonella typhimurium - Endang Warsiki, Mulyorini Rahayuningsih, dan Roseiga Retno Anggarani (Jurnal Teknologi Industri Pertanian, 2016)
Smart label is a label which could inform the quality and provide safety assurance of the food product.In this research, the label was produced from colored media and purposed to detect the growth of Salmonella.typhimurium. This bacterium is a pathogenic bacterium that causes salmonellasis disease with symptoms ofpoisoning type of infection. This bacterium is commonly appear in the fresh meat and meat product. The rapiddetection of this bacterium would assure the freshness and safety of the meat. This research was aimed toproduce the media based in color changing for rapid detection of the presence of S. typhimurium. The mediaindicator was produced from 2% (w/v) agar powder, 0.5% (w/v) tapioca starch, 1% (w/v) glycerol and 1% (w/v)selective media and then dissolved into distilled water until 100 mL solution. Four kind of selective medias wereused, i.e. Xylose Lysine Deoxychoalate agar (XLD), Hektoen Enteric Agar (HEA), Salmonella Shigela Agar(SSA) and Bismuth Salt Agar (BSA). XLD media was found to be a very sensitive media to the S. typhimuriumgrowth and presented a transparent color change to pink color that can be seen visually. The concentrationrange of 1-1.5% (w/v) of XLD was the best to develop the media. On the other hand, BSA and SSA media wasnotsensitiveon the S. typhimurium. Furthermore, another enrichment media of Brain Heart Infussion (BHI) withphenol red indicator has resulted in the rapid detection of 24 h after incubation compare to media without BHIin the same time. This media indicator gave in changing color from red to yellow.Keywords: media indicator, selective media, color changing, S. typhimurium